Implementation of an Integrative Approach to Improving Students' Reading Comprehension Skills in Grade IV of SD 69 Ambon - Nohra Sampulawan; Sarah Sahetapy; Ribka, L. Ririhena (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to describe ways to improve the reading comprehension skills of fourth-grade students of SD 69 Ambon. This research is motivated by the low reading skills of fourth-grade students of SD 69. This can be seen from the results of initial observations of 25 fourth-grade students, only 5 students are categorized as very good. So it is necessary to find a way to improve students' reading comprehension skills. This study uses classroom action research (CAR) which has stages of planning, action, observation, and reflection. The data of this study were obtained by observation and documentation. The results of the study indicate that there is an increase in the reading comprehension skills of fourth-grade students of elementary school, it can be seen from the results of observations in cycle I meeting I observation results of 64%, in cycle I meeting II there is an increase so that the observation results are 65.3%. Furthermore, in cycle II meeting I get observation results of 70%, in cycle II meeting II there is an increase so that the observation results are 81.66%. From the results of the study it can be concluded that actions by applying an interactive approach can improve students' reading comprehension